Physicochemical Quality of Total Mixed Ration Silages Based on Cynodon dactylon and Gliricidia sepium - Hutabarat, Amelia Lulu Rosalin; Lestari, Wenni Meika; Ali, Abdul Muta; Sabina, Putri (Jurnal Sain Peternakan Indonesia, 2023)
A mixture of legumes with grasses has been shown to improve silage's physical and nutritional qualities. This study assessed the chemical composition and physical characteristics of Cynodon dactylon (CD) when mixed with different proportions of Gliricidia sepium (GS). Chopped and wilted leaves of CD and GS were mixed in the following combinations:  P1: 0% GS + 78% CD; P2: 28% GS + 50% CD; P3: 39% GS + 39% CD; P4: 50% GS + 28% CD; P5: 78% GS + 0% CD. Each combination is enriched with 10% rice bran (RB), 10% Corn Feed (CF) and 2% molasses. A 750 g of the fresh materials were compressed into plastic jar silos and kept for 21 days. The physical characteristics and the loss of chemical composition of silage were analyzed descriptively. pH value and the chemical composition data were subjected to analysis of variance (ANOVA) in a randomized complete design with five replications. Considering all physical and chemical characteristics, GS and CD can be combined as silage material. However, the study recommends including 28-39% GS (P2 and P3) as the most suitable in response to pH value, color, aroma, texture, and presence of fungus.